Development of a Functional Food Additive from Underutilized Crops; Turkey Berry and Aidan Fruit - Davis Eunice (University of Cape Coast, 2025)
The demand for natural food additives is rising as consumers increasingly seek healthier, safer alternatives to synthetic compounds. Natural additives play a vital role in enhancing food quality, extending shelf life, and contributing to dietary diversity, aligning with efforts to address global food challenges. Aidan and turkey berries remain underutilized fruits, with excellent macro and micronutrients, as well as phytochemical and antimicrobial properties. However, little research focuses on the potential of formulating a functional product as well as the proximate, physicochemical, and phytochemical properties of the crops. Hence, the present study was designed to develop a functional food additive from Aidan fruit and turkey berry. Eight samples including single (Aidan and turkey berry) as well as composite blends of these fruits were formulated and assessed for physicochemical, phytochemical, and sensory properties using a completely randomized design. Results revealed significant variations in proximate and phytochemical properties of Aidan fruit and turkey berry. Typically, turkey berries had 6.10%, 3.18%, and 7.37% increase in moisture, ash, and protein relative to Aidan fruit (4.49%, 2.09% and 6.57%) respectively. Similarly, 36.9%, 159.1%, and 142.6% increases in flavonoid, phenol, and carotenoid were recorded in aidan fruit compared to turkey berry (22.54%, 97.7% and 133.6%) respectively. Furthermore, the results indicated that a composite of turkey berry and aidan fruit tends to improve the phytochemical, proximate, and sensory attributes of formulated functional products. It was clear that, the proximate, phytochemical, and mineral composition of functional product showed a direct association with University of Cape Coast https://ir.ucc.edu.gh/xmlui Digitized by Sam Jonah Library iv increasing turkey berry proportion within the composition. Thus, properties such as ash, fiber and moisture content, increased with increasing turkey berry in the composition. Similarly, carotenoids, flavonoid and phenolic properties were higher with samples of higher proportion of aidan fruit compared to turkey berry. Regarding sensory attributes, taste, texture, appearance, aroma and overall acceptability, they were significantly higher for samples T(90):A(10) and T(82.5):A(17.5), compared to samples T(0):A(100) and T(100):A(0). Additionally, functional products formulated from composition recorded higher overall acceptability compared to single products. These findings emphasize the promising role of Aidan and turkey berry as sustainable, nutrient-rich natural additives, offering a pathway to improve food quality and health outcomes. Also, it was clear that a blending of aidan fruit and turkey berry significantly improves nutritional quality but this is contingent of proportion in the blend. Despite the aforementioned, further studies could explore how various processing techniques and storage conditions could influence quality parameters of the functional product
xii,111p:,ill